Association Between Psychological Profile And Academic Achievement of Midwifery Students - Rahmatul Ulya; Arni Amir; Yaslinda Yaunin (Universitas Andalas, 2018)
One way to reduce MMR and IMR is to improve the quality of graduates of midwifery education. The development of students' abilities can be evaluated by seeing the results or learning achievements. Psychological tests will help midwifery education institutions to find out the background, motivation and other environments related to students. This research is a quantitative research design with a cross sectional design to determine the association between psychological profiles with the academic achievement of midwifery students. The study was conducted in November - December 2017 at the West Sumatra Midwifery Academy. The population in this study were all 2nd grade students totaling 40 people. Statistical analysis was conducted using chi square analysis. The results of this study were: 70.0% of the subjects structure of intelligence were in the sufficient category, 62.5% of the subjects work behavior were in the sufficient category, 72.5% of the subjects sociability were in the sufficient category, 50.0% of subjects leadership were in the less category, 47, 5% of the subjects temprament and emotion were in the sufficient category, 60.0% of the subjects grade point average (GPA) is sufficient. There was a significant relationship between the structure of intelligence, work behavior, type of personality, sociability, leadership, temperament and emotions with the academic achievement of midwifery students.